2013
DOI: 10.1080/17458080.2013.843209
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterisation andin vitrocytotoxicity studies of chelerythrine-loaded magnetic Fe3O4@O-carboxymethylchitosan nanoparticles

Abstract: In this work, a novel, active tumour-targeting system (Fe 3 O 4 @OCMCS-CHE) was designed by surface-modifying superparamagnetic iron oxide nanoparticles (Fe 3 O 4 ) with O-carboxymethylchitosan (OCMCS) to improve their biocompatibility and ability to target specific tumour cells. The chelerythrine (CHE) was used as the model of anti-tumour drug in this system. The optimised formulation was characterised and confirmed by scanning electron microscopy (SEM), transmission electron microscope (TEM), vibrating sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Thus, nanocarriers can increase the cell cytotoxicity of the drug against HT-29 cells, and there is a dose-dependent and relatively time-dependent manner regarding using complex. These results confirm the previous studies reported that the cytotoxicity of the drug-loaded MNNPs follows dose-dependent and time-dependent trends ( Huang et al, 2015 ; Dhavale et al, 2021 ). The IC50 of the MNNPs complex was observed at 40 μg/mL within 48 h, therefore this concentration was considered for the following tests.…”
Section: Resultssupporting
confidence: 93%
“…Thus, nanocarriers can increase the cell cytotoxicity of the drug against HT-29 cells, and there is a dose-dependent and relatively time-dependent manner regarding using complex. These results confirm the previous studies reported that the cytotoxicity of the drug-loaded MNNPs follows dose-dependent and time-dependent trends ( Huang et al, 2015 ; Dhavale et al, 2021 ). The IC50 of the MNNPs complex was observed at 40 μg/mL within 48 h, therefore this concentration was considered for the following tests.…”
Section: Resultssupporting
confidence: 93%
“…It showed that higher drug loading content was achieved when the microparticles were obtained at lower ultrasonic time for higher oil/water ratio. The drug loading content of this nanoparticles was much higher than that of Fe3O4@O‐carboxymethyl chitosan nanoparticles …”
Section: Resultsmentioning
confidence: 90%